CSIG-15. ALTERATIONS IN THE TRANSSULFURATION PATHWAY ENABLE GLIOBLASTOMA INVASION INTO THE PERITUMORAL WHITE MATTER. (12th November 2021) - Garcia, Joseph; Jain, Saket; Akins, Erin; Beniwal, Angad; Spatz, Jordan; Gill, Sabraj; Wolf, Kayla; Cha, Junghwa; Kumar, Sanjay; Aghi, Manish K
Abstract: Glioblastoma is a primary malignant brain tumor with a median survival under two years. The poor prognosis glioblastoma caries is largely due to cellular invasion, which enables escape from resection and drives inevitable recurrence. While numerous factors have been proposed as the primary driving forces behind glioblastoma's ability to invade adjacent tissues rapidly, little attention has been paid to the alterations in tumor cell metabolism needed for tumor cells to thrive in isolation in the peritumoral white matter. To improve on biased 2D cell culture studies, we defined the links between glioblastoma metabolism in invasion using unbiased CRISPR screens and metabolomics performed in biomimetic 3D hydrogels and regional biopsies of patient glioblastomas. Through these platforms, we identified targetable metabolic factors which drive cellular invasion in glioblastoma. Metabolomics revealed cystathionine to be selectively enriched in the invasive tumor front of both site-directed biopsies (6-fold change), and 3D organoid models (14-fold change). RNA sequencing revealed 7/30 (23%) metabolic genes upregulated in the invasive tumor front were involved in cysteine or glutathione metabolism. These results highlight a clear role of the transsulfuration pathway in glioblastoma invasion, revealing a targetable alteration unique to invading glioblastoma cells.